Impact of oral health conditions on school performance and lost school days by children and adolescents: what are the actual pieces of evidence? - Janice Simpson de Paula; Fábio Luiz Mialhe (Universidade Estadual de Campinas, 2015)
Aim: To investigate evidence of associations between oral health status of children and adolescents and their school performance and lost school days due to dental problems. Methods: PubMed electronic database was searched for scientific papers published between 1990 and 2013. Twenty-one papers that attempted to investigate the impact of oral health on school performance and lost school days were retrieved. Brief descriptions of each study's methodology and outcomes were presented and discussed. Results: Although the papers reported statistically significant associations between school performance or lost school days and oral health conditions of schoolchildren, all of them were cross-sectional and ecological studies with an observational design, which may not provide full information about causes and effects. In addition, the lack of standardized criteria did not allow comparisons among the studies retrieved in the search. Conclusions: Oral diseases appear to impact on lost school days and school performance of children and policy-makers should address this issue when planning health promotion interventions in school settings. However, standardized materials and methodologies as well as longitudinal studies using valid and reliable criteria are needed to confirm the causes or risks of oral health factors in school performance, generating hypotheses for future research and providing important data for determining effective actions in school health programs.